Kajian Teologis Amsal 4:23 “From Scroll to Soul Srategi Menjaga Iman Ditengah Arus Informasi Media Sosial” - Yoram Kodea (International Forum of Researchers and Lecturers, 2026)
Digital spirituality is a way of living and expressing spiritual life within the context of the digital world, where technology serves as a medium to strengthen one’s relationship with God, oneself, and the community. It is therefore a conscious effort to maintain and nurture faith amid the overwhelming flow of information on social media. The concept of From Scroll to Soul encourages believers not merely to be passive recipients of information but to engage spiritually by using technology as a tool for faith formation. Practices such as using spiritual apps, participating in online communities, selecting constructive content, and conducting digital detoxes are important steps to maintain focus on God. Theologically, digital spirituality affirms that God is present in every aspect of life, including virtual spaces. Technology can become a tool of grace that deepens one’s relationship with God and serves as a space for witnessing faith when used wisely. Thus, digital spirituality is not a rejection of technology but rather its use as a medium for growth, testimony, and bringing Christ’s values into the modern information culture.